2011
DOI: 10.1002/mc.20762
|View full text |Cite
|
Sign up to set email alerts
|

β‐Escin sodium inhibits inducible nitric oxide synthase expression via downregulation of the JAK/STAT pathway in A549 cells

Abstract: β-escin, a triterpene saponin, is one of the major active compounds extracted from horse chestnut (Aesculus hippocastanum) seed. Previous work has found that β-escin sodium has antiinflammatory and antitumor effects. In the present study, we investigated its effect on cell proliferation and inducible nitric-oxide synthase (iNOS) expression in human lung carcinoma A549 cells. β-escin sodium (5-40 µg/mL) inhibited cytokine mixture (CM)-induced nitric oxide (NO) production in A549 cells by reducing the expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 32 publications
1
21
0
Order By: Relevance
“…This study is consistent with the earlier observations that support possible antitumorigenic effects of b-escin in in vitro and in vivo models (6)(7)(8)(9)(10). Previously, we showed that b-escin, at 250 and 500 ppm in the diet, inhibited colon carcinogen-induced preneoplastic foci in rat colon in a dose-dependent manner (6).…”
Section: Discussionsupporting
confidence: 92%
“…This study is consistent with the earlier observations that support possible antitumorigenic effects of b-escin in in vitro and in vivo models (6)(7)(8)(9)(10). Previously, we showed that b-escin, at 250 and 500 ppm in the diet, inhibited colon carcinogen-induced preneoplastic foci in rat colon in a dose-dependent manner (6).…”
Section: Discussionsupporting
confidence: 92%
“…Escin has been reported to exhibit antitumor eVects in various cancer cells and synergize with paclitaxel and doxorubicin in human hepatocellular carcinoma cells (Tan et al 2010;Patlolla et al 2006;Ji et al 2011;Zhou et al 2009;Shen et al 2011;Ming et al 2010). However, the eVect of escin against human pancreatic cancer cells is not known.…”
Section: Discussionmentioning
confidence: 99%
“…1), a natural mixture of triterpene saponins isolated from Aesculus wilsonii Rehd, has been demonstrated to possess anti-cancer activity by the induction of growth inhibition and apoptosis in many human cancer cells in recent years (Tan et al 2010;Patlolla et al 2006;Ji et al 2011;Zhou et al 2009;Shen et al 2011). Another recent study indicated that escin could inhibit proliferation and substantially enhance cytotoxicity of paclitaxel and doxorubicin in human hepatocellular carcinoma cells by down-regulating Cyclin D1, Bcl-2, Bcl-xL, Survivin, Mcl-1 and VEGF (Ming et al 2010).…”
Section: Introductionmentioning
confidence: 96%
“…Shen et al [23] reported that treatment of human cholangiocarcinoma cell lines QBC939, Sk-ChA-1, and MZ-ChA-1 with β-escin induces growth arrest and increases apoptosis with collapse of the mitochondrial membrane potential and the activation of the caspase-3 pathway. Ji et al [24] showed that β-escin inhibits nitric oxide (NO) production and growth of A549 human lung cancer cells by suppressing the JAK/STAT/inducible nitric oxide (iNOS) signaling pathway. Wang et al [25•] revealed that β-escin can potentiate the anti-cancer effect of gemcitabine in pancreatic cancer cell lines.…”
Section: In Vitro Anti-cancer Properties Of β-Escinmentioning
confidence: 99%